Peran Orang Tua Dalam Proses Pembelajaran Anak Pada Kelompok B Di Paud Rahayu Kota Bengkulu - Hanafi, Rike Syafitri; Margaretha, Lydia; Rulismi, Dwi (Early Childhood Research and Practice, 2025)
This research aims to describe and gain knowledge about the role of parents in the learning process of early childhood students at PAUD Rahayu Bengkulu City. This study utilizes field research with a qualitative descriptive approach and employs data collection methods, namely interviews, observation, and documentation. The subjects of the research are individuals, places, or objects that are observed; specifically, the subjects targeted for this study are the parents of the children and the teachers at PAUD Rahayu Bengkulu City. The analysis technique used includes data reduction, data presentation, and conclusions. The research shows how parents act as guides, as indicated by interviews with three parents who provide methods and strategies to assist their children in learning. Based on the interviews, the role of parents as facilitators includes providing resources for children at school and home. Additionally, according to the interviews, parents also serve as motivators by giving encouragement and advice, as well as teaching manners. Lastly, based on the interviews, parents act as educators capable of assisting their children in completing tasks at PAUD Rahayu Bengkulu City.